Retooling and re-skilling of cataloguing librarians in the digital era: An insight from Nigeria - Olayemi, Kemi Jummai; Olayemi, Olalekan Moses; Michael, Juliana Patrick (Record and Library Journal, 2025)
Background of the study: The digital transformation of library resources and users has introduced significant changes to the cataloguing process, necessitating a retooling and re-skilling of cataloguing librarians to keep pace with evolving technologies and practices. Purpose: The study was designed to investigate the issues associated with retooling and re-skilling cataloguing librarians in the digital era. Method: This study adopted a mixed method, incorporating both quantitative and qualitative research approaches. The study population comprised cataloguers across libraries in Nigeria. For the quantitative component, a structured questionnaire was used, while the qualitative aspect involved semi-structured interviews with selected participants to gain deeper insights and clarification on certain responses provided in the questionnaire. Findings: The findings demonstrated that the majority of the respondents indicated that they are already applying some digital tools, such as computers, the internet, and library software management to cataloguing library materials due to their availability, while a few are yet to. The findings showed that a majority of the cataloguers possess digital skills, but many still have low skills for creating metadata for digital resources. The study also revealed that respondents’ perceived implications of the digital era for cataloguing practice can lead to new roles and responsibilities, organizational changes, copy cataloguing, and the introduction of non-professionals and non-cataloguers to cataloguing profession. Conclusion: Based on the findings, the study concludes that a majority of Nigerian cataloguers have embraced the use of digital tools in cataloguing, and possess the digital skills required for the digital era.